Non-puerperal uterine inversion caused by a leiomyoma - Soukaina, Fekkoul; Inas, Rhazi; Hafsa, Taheri; Hanane, Saadi; Ahmed, Mimouni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine inversion is characterized by the invagination of the fundus of the uterus through the vagina. It’s a rare postpartum complication leading to massive bleeding and it’s extremely rare in non-puerperal cases. Non-puerperal uterine inversion is caused by tumors exerting force on the fundus of the uterus, turning the uterus inside out. It is most frequently associated with benign tumors such as submucosal leiomyomas however, malignant tumors can also be associated. We reported the case of 43-year-old women, G1P1, who was admitted at the emergency department for a bleeding vaginal prolapsed mass. A pelvic MRI performed revealing a complete uterine inversion probably due to a submucous myoma or a malignant process. She underwent a total abdominal hysterectomy with bilateral salpingectomy by both natural and abdominal way. Pathological study revealed a degenerating leiomyoma. The patient recovered well from the operation with no complications.